Genetic changes in progeny of bystander human fibroblasts after microbeam irradiation with X-rays, protons or carbon ions: The relevance to cancer risk. (January 2015) - Autsavapromporn, Narongchai; Plante, Ianik; Liu, Cuihua; Konishi, Teruaki; Usami, Noriko; Funayama, Tomoo; Azzam, Edouard I.; Murakami, Takeshi; Suzuki, Masao
Abstract Purpose: Radiation-induced bystander effects have important implications in radiotherapy. Their persistence in normal cells may contribute to risk of health hazards, including cancer. This study investigates the role of radiation quality and gap junction intercellular communication (GJIC) in the propagation of harmful effects in progeny of bystander cells. Materials and methods: Confluent human skin fibroblasts were exposed to microbeam radiations with different linear energy transfer (LET) at mean absorbed doses of 0.4 Gy by which 0.036–0.4% of the cells were directly targeted by radiation. Following 20 population doublings, the cells were harvested and assayed for micronucleus formation, gene mutation and protein oxidation. Results: Our results showed that expression of stressful effects in the progeny of bystander cells is dependent on LET. The progeny of bystander cells exposed to X-rays (LET ∼6 keV/μm) or protons (LET ∼11 keV/μm) showed persistent oxidative stress, which correlated with increased micronucleus formation and mutation at the hypoxanthine-guanine phosphoribosyl-transferase (HPRT) locus. Such effects were not observed after irradiation by carbon ions (LET ∼103 keV/μm). Interestingly, progeny of bystander cells from cultures exposed to protons or carbon ions under conditions where GJIC was inhibited harbored reduced oxidative and genetic damage. This mitigating effect was not detected when the cultures were exposed to X-rays. Conclusions: These findings suggest that cellular exposure to proton and heavy charged particle with LET properties similar to those used here can reduce the risk of lesions associated with cancer. The ability of cells to communicate via gap junctions at the time of irradiation appears to impact residual damage in progeny of bystander cells.